The potato pest Russelliana solanicola Tuthill (Hemiptera: Psylloidea): taxonomy and host-plant patterns - Serbina, Liliya; Burckhardt, Daniel; Birkhofer, Klaus; Syfert, Mindy M.; Halbert, Susan E. (Zootaxa, 2015)
The Neotropical jumping plant-louse Russelliana solanicola Tuthill is a potato pest and a probable vector of plant pathogens. Populations morphologically similar to those found on potatoes have been collected on plants of at least ten different families, four of which have been confirmed as hosts by the presence of immatures. This suggests that R. solanicola is either a single polyphagous species or a complex of closely related, monophagous species (host races/cryptic species). Results of our analyses of multiple morphometric characters show for both sexes a grouping of the populations of R. solanicola and a clear separation of the latter from other Russelliana species. On the other hand, within R. solanicola, there is an overlap of populations from different host-plants as well as from different geographical regions. The results of the present study strongly suggest that R. solanicola is a single, polyphagous species and the known distribution indicates that it is native to the Andes. It is likely that R. solanicola has been introduced into eastern Argentina, Brazil and Uruguay. The polyphagy together with the ability to disperse and transmit plant pathogens potentially make this species an economically important pest of potato and other crop species.